Anti-Hypertensive Effect of Nigella Sativa Seeds in Patients with Hypertension - Siddiqui, Amer Hassan; Khan, Nadiya; Naseer, Shafia; Malkera, Arooj; Akbar Khan, Shazia; Ahsan, Ifra; Israr, Mohammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypertension (HTN) is an important public health problem. Antihypertensive drugs lead to side effects, possibly leading to non-compliance, thus uncontrolled hypertension as well as cardiovascular morbidity enhanced risk and death. Aim: To determine the effect of nigella sativa seeds in patients with hypertension at 0, 6 and 12 weeks; and to compare these effects with control patients on standard hypertension therapy. Study Design: Experimental study. Methodology: Present study enrolled 200 patients with hypertension (100 cases and 100 controls) visiting Services Hospital Lahore. Nigella sativa seeds were administered to 100 hypertensive patients who were on standard therapy in a dose of 1.5gms (once daily) orally for 12 weeks. Their blood pressure was recorded and compared to the 100 patients in control group taking standard therapy only at 0, 6, 12 weeks. Data was collected through questionnaire which was entered in computer using SPSS Results: Among cases, mean age was 45.16±10.544 years while in controls was 41.61±10.971 years. In case group, at 0 week, 6 weeks and 12 weeks, the mean systolic blood pressure (mmHg) was 139.49±6.337, 137.87±5.829 and 132.66±5.887 while mean diastolic blood pressure was 102.32±6.135, 100.58+6.081 and 95.26±6.594, respectively. In control group at 0 week, 6 weeks and 12 weeks, the mean systolic blood pressure (mmHg) was 139.07±6.307, 138.93±6.961 and 133.37±5.836 while mean diastolic blood pressure was 102.85±5.844, 102.75±5.518 and 95.64±6.850, respectively. Conclusion: We concluded that Nigella Sativa seeds have anti-hypertensive effect and significantly reduce the blood pressure among patients with hypertension.